2022
DOI: 10.1049/bme2.12076
|View full text |Cite
|
Sign up to set email alerts
|

Breast mass classification based on supervised contrastive learning and multi‐view consistency penalty on mammography

Abstract: Breast cancer accounts for the largest number of patients among all cancers in the world. Intervention treatment for early breast cancer can dramatically extend a woman's 5‐year survival rate. However, the lack of public available breast mammography databases in the field of Computer‐aided Diagnosis and the insufficient feature extraction ability from breast mammography limit the diagnostic performance of breast cancer. In this paper, A novel classification algorithm based on Convolutional Neural Network (CNN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Yan et al proposes an ROI-level contrastive and classification loss for a combined breast mass detection and classification task in full DM images 10 . Similar approaches have also been used by Sun et al and You et al, where a multi-view contrastive loss in addition to the classification loss is suggested 9,11 . However, none of the works has explored the advantages of using SSL-guided classification for CESM ROI classifications.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Yan et al proposes an ROI-level contrastive and classification loss for a combined breast mass detection and classification task in full DM images 10 . Similar approaches have also been used by Sun et al and You et al, where a multi-view contrastive loss in addition to the classification loss is suggested 9,11 . However, none of the works has explored the advantages of using SSL-guided classification for CESM ROI classifications.…”
Section: Introductionmentioning
confidence: 96%
“…Alternatively, contrastive learning-based methods which leverage class label information tackle the problem of learning meaningful representations while mitigating the challenge of data availability 7 . Multiple works have explored various SSL and supervised contrastive learning methods in digital mammography analysis [8][9][10][11] . For example, Cao et al presents an SCL method in multi-view DM images for BIRADS analysis 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other studies have shown that precancerous mammograms contain unique imaging information beyond breast density that can be used for risk assessment of breast cancer (Hinton et al 2019;Yala et al 2019;Dembrower et al 2020;Yala et al 2021). Sun et al extracted the complementary information between CC and MLO mammographic views of a breast mass, greatly improving the classi cation performance and diagnostic speed of mammographic breast mass (Sun et al 2022). In addition to their utility in risk assessment, parenchymal and texture features can help evaluate and predict breast cancer (Peter et al 2019).…”
Section: Introductionmentioning
confidence: 99%